Effects of single-dose morning and evening administration of pravastatin on antioxidant markers in cholesterol-fed rabbits - Kamal S (Dove Medical Press, 2011)
Sahar Mohamed KamalDepartment of Pharmacology, Faculty of Medicine, Ain Shams University, Cairo, EgyptBackground: Accurate timing of statin administration is considered important to obtain the best hypolipidemic effect. Pravastatin is one of the currently prescribed hepatic 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, and was chosen in this study to evaluate its antioxidant effect when administered as a single daily dose in the morning versus evening in cholesterol-fed rabbits.Methods: This 12-week study was performed in New Zealand rabbits, divided into four groups (n = 6 each), ie, normocholesterolemic controls; cholesterol 1% diet, nontreated ; cholesterol 1% diet treated with pravastatin in the morning; and cholesterol 1% diet treated with pravastatin in the evening. Plasma total cholesterol levels, superoxide dismutase enzyme levels in erythrocyte lysates, thiobarbituric acid-reactive substance content, catalase, and glutathione enzyme activity in liver homogenates from the tested rabbits were measured.Results: Both morning and evening treatment with pravastatin significantly improved all the measured antioxidant markers in comparison with nontreated cholesterol-fed rabbits. However, results obtained with evening dosing were better than with morning dosing.Conclusion: The antioxidant profile of pravastatin is better when the drug is administered in the evening rather than in the morning.Keywords: pravastatin, chronotherapy, antioxidant markers, cholesterol-fed rabbits